REGIONAL DIVERSIFICATION OF THE LEVEL OF ECONOMIC DEVELOPMENT IN POLAND - Kowalik, Jan; Zawada, Marcin; Kucęba, Robert (PEOPLE: International Journal of Social Sciences, 2017)
In the modern world economy, the importance of regions and cities in economic development is increasing. In line with the policy of the European Union, efforts to level out regional developmental disparities should be made. Regional development can be explored in terms of social, economic or environmental aspects, satisfaction with the level and quality of life of inhabitants, and development of social capital. The aim of this study is to assess only the current level of economic development and its differentiation in various regions of Poland. Data from the Local Data Bank of the Central Statistical Office from the years 2007-2015 have been used in the analysis. Obtained results will allow to draw conclusions about regional policy in Poland.